ANALISIS KEKUATAN DINDING MORTAR COR DI TEMPAT DENGAN PERKUATAN TULANGAN VERTIKAL DAN BALOK-KOLOM PRECAST AKIBAT BEBAN STATIK - , NOVAN BUDI ARDIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In Indonesia, concrete bricks have often used as main material to construct simple houses wall. However instead of using concrete bricks, this research propose mortar as an alternative. The mortar were casted in place to form a wall. Steel reinforcement bars are placed in vertically to provide wallâs additional strength. The research aims to examine how better this alternative compare to the common concrete brick walls. In this research, dimension of two wall specimens is 150 cm 150 cm with 10 cm thick. Variation of specimens, namely: mortar wall with vertical reinforcement steel bar Ã6-500 mm and concrete masonry wall without reinforcement steel bar. Specimens have made with beam-column precast system. Two specimens of wall was tested with a static lateral load in the strong direction axis of the wall based on ASTM E 564-00. The data of test results for two variations of the wall have been compared. Then, the results have been compared by simple analysis using Microsoft Excel 2007 software. The result of research, testing load capacity of mortar wall with vertical reinforcement steel bar (DMTV) Ã6-500 mm: first crack condition 23,46 kN, yield condition 29,42 kN, and ultimate condition 45,42 kN. Whereas the testing load capacity of concrete masonry wall without reinforcement : yield condition 21,96 kN and ultimate condition 37,99 kN. The result of a simple analytical comparison between each of the wall, load capacity of DMTV Ã6-500 mm: first crack condition 116,838%